BIBLIOMETRIK STUDI TENTANG KONSELING ISLAM DALAM MENDUKUNG KARIR IBU RUMAH TANGGA BERPENDIDIKAN - Harahap, Nurintan Muliani; Siti Wahyuni Siregar (Universitas Islam Ahmad Dahlan, 2024)
This research aims to understand the role of Islamic counseling in supporting the careers of educated housewives who play dual roles as mothers and workers. The issue raised is how Islamic counseling helps women face the challenges of balancing career and family life. The research objectives also include how such counseling impacts women's emotional and psychological well-being. The method used is a qualitative approach with bibliometric analysis. Data were collected through a literature search from the Scopus and Google Scholar databases, producing 34 relevant articles based on keywords such as